EKSTRAK JAHE LEBIH EFEKTIF DALAM MENGURANGI MUAL PADA KEHAMILAN TRIMESTER I DIBANDINGKAN DENGAN VITAMIN B6 - Nanny Lia Dewi, Vivian; Dewi Anggraeni, Fatimah (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
Background: Nausea and vomiting on pregnant women cause disruption of daily activities and may be harmful for both mother and fetus, for example chronic weight loss, which further leads to intrauterine growth retardation. Ginger as one of the herbals has various advantages compared to other herbs, especially for pregnant women who experience nausea and vomiting. Objectives: To determine the difference effect of ginger extract and B6 vitamin in reducing nausea in first term of pregnancy Methods: This research was a quasi experiment with pre and post-test control group design. Sample were 50 pregnant women whose pregnancy age were less than 12 weeks. This research involved 50 respondents, 25 in intervention group (using ginger extract) and the other 25 in control group (B6 vitamin). Data were collected by observation using visual analog scale of nausea in 30 minutes, 1 hour, and 2 hours after intervention. Data were analysed by paired and independent t-test. Results: There was difference in nausea score between intervention and control group, t-value= 2.435 and p= 0.019 in 30 minutes after usage. The range of nausea score in intervention group was 2.86 and in control group was 2.02. Conclusion: Ginger extract is more effective in reducing nausea during the first term of pregnancy than B6 vitamin in 30 minute after usage. Keywords: Ginger extract, B6 vitamin, nausea, pregnancy.